The influence of e-service quality, trust, brand image on Shopee customer satisfaction and loyalty - Dola Fitritha Raras Handayani; Retno Widowati PA; Nuryakin Nuryakin (Jurnal Siasat Bisnis, 2021)
Purpose: This research's main objective is to determine the relationship among e-service quality, trust, and brand image to customer loyalty. Customer satisfaction was a mediator which focused on Shopee customers in Yogyakarta.